Parent Cultural Adaptation and Child Functioning in Culturally Diverse, Urban Families of Preschoolers - Calzada, Esther J. (2009)
Parent cultural adaptation and preschool behavioral and socioemotional functioning were examined in a community sample of urban families from diverse cultural backgrounds. Participants were 130 families of children (mean age = 4.1 years) attending eight public Pre-Kindergarten programs in urban communities. Parents completed a measure of cultural adaptation that taps into acculturation and enculturation, and teachers reported on children’s externalizing problems, internalizing problems and adaptive behavior in the classroom. Parents’ ethnic identity was a significant predictor of children’s functioning. The retention of parents’ culture of origin and specific aspects of acculturation are related to positive outcomes in a sample of culturally diverse families of preschoolers living in urban communities. Bicultural parents (those with high ethnic and US American identity) had children with lower levels of internalizing problems and higher levels of adaptive behavior relative to parents who were not bicultural. Implications for enhancing positive child outcomes through the promotion of parental ethnic identity are discussed.